Develop data encryption by using mathematical complement - Malik, Azhar (Opción, 2019)
(Global auto orphic induction for number fields). - Let's be the numbers fields, E has the cyclic extensions of F, of it is degree. Auto orphic induc- tions associate to the cuspidor auto orphic representations of GLm (AE) an auto orphic representation π of GLmd (AF), induce from cuspidor, & characterize by a fact that the place v of F, a factor L (πv, s) is the product of the factors L (Tw, s), where w run inside a place of E above v. By a corres- pondences conjecture by Langland’s, that processes should corresponded to inducing Galois representation to E to F. They proved here that a representation π auto morphically induce from T exist, & study a fiber and image of auto orphic inductions. For that use Clozel on basic changes, which correspond to Galois representation from F - E, and clarified a relation between two processes. And proved that global auto-orphic inductions are compatible, at finite place, and a local auto orphic induction defines by R. Herb & author.